2012
DOI: 10.1371/journal.pone.0039141
|View full text |Cite
|
Sign up to set email alerts
|

TYK2 Kinase Activity Is Required for Functional Type I Interferon Responses In Vivo

Abstract: Tyrosine kinase 2 (TYK2) is a member of the Janus kinase (JAK) family and is involved in cytokine signalling. In vitro analyses suggest that TYK2 also has kinase-independent, i.e., non-canonical, functions. We have generated gene-targeted mice harbouring a mutation in the ATP-binding pocket of the kinase domain. The Tyk2 kinase-inactive ( Tyk2 K923E ) mice are viable and show no gross abnormalities. We show that kinase-active … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
58
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 63 publications
(107 reference statements)
5
58
0
Order By: Relevance
“…In line with this, GzmB and Prf1 expression were not altered in the absence of STAT1. 41 Similar to our earlier findings for IFNa/b 31 , we did not observe differences between Tyk2 ¡/¡ and Tyk2 K923E NK cells in canonical IL-12 signaling: STAT3 and STAT4 activation and IFNg production are severely impaired in both genotypes. We demonstrate that the requirement for TYK2 in the IL-12 signaling cascade is not due to an IL-12Rb1 scaffolding function.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In line with this, GzmB and Prf1 expression were not altered in the absence of STAT1. 41 Similar to our earlier findings for IFNa/b 31 , we did not observe differences between Tyk2 ¡/¡ and Tyk2 K923E NK cells in canonical IL-12 signaling: STAT3 and STAT4 activation and IFNg production are severely impaired in both genotypes. We demonstrate that the requirement for TYK2 in the IL-12 signaling cascade is not due to an IL-12Rb1 scaffolding function.…”
Section: Discussionsupporting
confidence: 90%
“…31 For pJAK2 analysis cells were lysed directly in 1 £ Laemmli sample buffer. Antibodies used were: pSTAT3 (Tyr705, CS#9131), STAT3 (CS#9132S), STAT4 (clone C46B10, CS#2653), pJAK2 (Tyr1008, D4A8, CS#8082), JAK2 (D2E12, CS#3230), GzmB (CS#4275) and Prf1 (CS#3693) all from Cell Signaling Technology; panERK (clone 16/ERK) and pSTAT4 (Tyr693, clone 38/pSTAT4) from BD Transduction Laboratories.…”
Section: Western Blotmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a kinase-inactive Tyk2 mouse line was published in which noncanonical, kinase-independent functions could not be observed with regard to type I IFN response and antiviral defense. 40 However, in line with our data, noncatalytic functions of human Jak1 and Tyk2 in the context of IFNAR1, IL-6, and IL-10 stimulation were reported, suggesting that 1 catalytically competent Jak is sufficient for signaling provided that its partner behaves as scaffold, even if inactive. 41,42 Investigation of a Jak3 activation-loop-defective mutant, YY1980/981FF, demonstrates that activation-loop tyrosines are not absolutely required for Jak3 catalytic function, whereas lysine mutation (K885A) in the ATP-binding pocket completely abrogates catalytic activity.…”
Section: /2supporting
confidence: 87%
“…Studies in mice have shown that the requirement for Tyk2 in signaling by type I IFN and other immune cytokines can be cellcontext dependent (2,3,53). Moreover, it is increasingly clear that the functional impact of many polymorphisms, notably in immune response imbalance, can differ according to cell or tissue types and their particular biological state.…”
mentioning
confidence: 99%